Implementation of Additive Ratio Assessment (ARAS) in Decision Support Systems for Wi-Fi Repeater Selection - Indra Nanda; Rhaishudin Jafar Rumandan; Alfry Aristo Jansen Sinlae (TEKNOLOGI DITERAPKAN DAN JURNAL SAINS KOMPUTER, 2022)
Wi-Fi repeater devices are important tools for individuals, agencies, and companies so that the desired areas can be connected to the internet. To select a Wi-Fi repeater, take care in selecting the right product for your needs. However, not everyone has knowledge regarding the specifications of a Wi-Fi repeater. This resulted in a long process of selecting a Wi-Fi repeater because they had to find information regarding the specifications of the product to be purchased. This has an impact on the length of the process of making decisions. The purpose of this research is to build a decision support system using the Multi-Attribute Decision Making (MADM) approach and the Additive Ratio Assessment (ARAS) method for selecting the right Wi-Fi repeater device as needed. Referring to the utility level of each alternative to determine the ranking, the ARAS technique has the ability to choose the best alternative. Using the ARAS approach for case studies, which is identical to manual calculations, the developed system produces the same results, according to the case studies that have been completed. The DSS developed is website-based, with main features including managing data extraction, data alternatives, value alternatives, ARAS calculation methods, and displaying the best alternative in the form of ranking. Additionally, testing utilizing black-box testing reveals that all of the evaluated functions can function as they should.